Análise e projeto de risers compósitos em catenária - Teófilo, Fábio Anderson Fonteles (2010)
The general objective of this project consists of studying the viability of the use of risers compósitos in catenary deep waters and to compare this alternative with the use of risers of steel (Steel Catenary Risers SCR). As objective specific they can be cited: 1) Existing study of the existing bibliography on risers of material compósitos for detailed identification of the potentialities and difficulties. 2) Characterization of the structural behavior of the compósitos strengthened for way staple fibres to apply analytical and/or computational models for simulation of the behavior. Nonlinear effect and dependents of the time of structural elements of material compósitos will be verified due to the operating shipment and the ambient actions. 3) Simulation of the behavior of riser compósito under extreme and operational conditions, including the determination of the useful life of riser. 4) Comparison of the results gotten with the results of risers of steel in catenary (SCR).